Rate-distortion theory for Gaussian multiterminal source coding systems with several side informations at the decoder - Oohama, Y. (IEEE transactions on information theory, 2005)
In this paper, we consider the separate coding problem for L+1 correlated Gaussian memoryless sources. We deal with the case where L sources work as partial side information at the decoder for the reconstruction of the remaining source. The determination problem of the rate-distortion region for this system is the so-called many-help-one problem and it has been known as a highly challenging problem for almost 20 years. In this paper, we give a partial solution to this problem. We determine the rate-distortion region in the case where the L sources working as partial side information are conditionally independent if the remaining source we wish to reconstruct is given. The additive white Gaussian noise CEO problem is a special case of this. We also discuss the relation of the result previous results of ours